2009
DOI: 10.1088/0031-9120/45/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the conservation of mechanical energy using video analysis: four cases

Abstract: Inexpensive video analysis technology now enables students to make precise measurements of an object's position at incremental times during its motion. Such capability now allows users to examine, rather than simply assume, energy conservation in a variety of situations commonly discussed in introductory physics courses. This article describes the use of video analysis software in studying energy conservation for (1) objects in freefall, (2) simple pendulums, (3) objects rolling down inclines, and (4) masses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 14 publications
1
36
0
9
Order By: Relevance
“…A new recreation place in the middle of Yogyakarta City. Trampoline in SKE is called Panggon Lunjak [7]. More clearly this research is illustrated using a flow chart as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…A new recreation place in the middle of Yogyakarta City. Trampoline in SKE is called Panggon Lunjak [7]. More clearly this research is illustrated using a flow chart as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…De acordo com a experiência dos autores, que inclui o uso do Tracker em aulas de Física em disciplinas de graduação (Engenharia e Física), pós-graduação (mestrado profissional em Ensino) e ensino médio, a videoanálise constitui tecnologia de fácil aprendizado, tanto por parte de professores quanto estudantes, e que pode ser incorporada às aulas de Física após algumas horas de estudo e de contato com o programa. Além disso, é crescente o número de artigos em que são apresentadas novas metodologias e atividades experimentais mediadas por videoanálise, especialmente o Tracker, de modo que há uma comunidade em expansão a dar instrução e apoio às iniciativas de utilizar tal tecnologia em sala de aula (BROWN;COX, 2009;BRYAN, 2010;PHOMMARACH et al, 2012;BEZERRA et al, 2012;SIRISATHITKUL et al, 2013;WRASSE et al, 2014;SILVA;LIMA, 2017;BONATO et al, 2017;SILVA, 2018). Essa, certamente, é uma característica que favorece sua apropriação por parte dos professores e que torna viável seu emprego na sala de aula.…”
Section: Videoanálise E O Software Trackerunclassified
“…A referida técnica pode ser definida como sendo a investigação de um fenômeno físico por meio de sua filmagem, considerando a análise desse filme a partir de ferramentas computacionais que permitam o estudo de grandezas físicas relevantes para o seu entendimento [8][9][10][11]. As aplicações mais frequentes são em problemas clássicos de cinemática e dinâmica [5][6][7][8][9][12][13][14][15][16]. Contudo, trabalhos envolvendo física ondulatória, experimento de Millikan, práticas esportivas, entre outras aplicações, também são encontrados na literatura dedicada ao tema [11,[17][18][19][20][21].…”
Section: Videoanálise Do Movimento Da Rodaunclassified